Optimizing maize yields using growth stimulants under the strategy of replacing chemicals with biological fertilizers - Abdo, Ahmed I.; El-Sobky, El-Sayed E. A.; Zhang, Jiaen (Frontiers in Plant Science, 2022)
Partial replacement of chemicals with biological fertilizers is a recommended strategy to reduce the adverse environmental effects of chemical fertilizer losses. Enhancing the reduced mineral with biological fertilizers strategy by foliar application of humic acid (HA) and amino acids (AA) can reduce environmental hazards, while improving maize (Zea mays L.) production under semiarid conditions. The recommended doses of N, P and K (e.g., 286 kg N ha-1, 75 kg P2O5 ha-1 and 67 kg K2O ha-1) were applied as the first fertilization level (100% NPK) and were replaced with biofertilizers by 100%, 75%, 50% and 25% as levels of reducing mineral fertilization. These treatments were applied under four foliar applications of tap water (TW), HA, AA and a mixture of HA and AA. Our results reported significant reductions in all parameters, including maize ear yield attributes and grain nutrient uptake, when replacing the mineral NPK with biofertilizers by 25-100% replacement. However, these reductions were mitigated significantly under the application of growth stimulants in the descending order: HA and AA mixture>AA>HA>TA. Applying a mixture of HA and AA with 75% NPK + biofertilizers increased ear length, grain yield, grain uptake of N and K, and crude protein yield by 37, 3, 4, 11 and 7%, respectively as compared with 100% mineral fertilizer only. Moreover, all investigated parameters were maximized under the application of 75% NPK + biofertilizers combined with AA or the mixture of HA and AA, which reveals the importance of growth stimulants in enhancing the reduced chemical NPK strategy. It could be concluded that the mineral NPK rate can be reduced by 25% with biofertilization without any yield losses when combined with HA and AA under arid and semi-arid conditions. That achieves the dual goals of sustainable agriculture by improving yield, while reducing environmental adverse effects.